Implementasi Augmented Reality Pengenalan Hewan, Buah dan Kendaraan Untuk Pendidikan Usia Dini - Riyanto Riyanto; Aries Suharso (Maranatha University Press, 2022)
As a result of the implementation of social distancing rules, the education sector is forced to implement the Distance Learning system or study from home which sometimes makes students feel bored in its implementation. Therefore, an alternative learning media is needed to overcome this boredom. One method that can be used is learning through applications with the addition of augmented reality technology. The purpose of this study was to design an interactive learning media for early childhood based on augmented reality technology and to determine the impact of its use. This type of research is action research, while the software development method used is the waterfall model. This app is designed using Unity 3D and Vuforia SDK. The results of the calculation of the questionnaire, obtained a value of 98.6% which means the application is included in the very effective criteria according to the Likert Scale. And from the results of the paired t-test of application users before and after using the application, it was concluded that there were differences in the assessment of learning outcomes before and after using augmented reality-based basic learning applications for early childhood.